Cannabis for Chronic Pain: Case Series and Implications for Clinicians. (1st June 2002) - Ware, Mark A; Gamsa, Ann; Persson, Jan; Fitzcharles, Mary-Ann
Abstract : BACKGROUND: Chronic pain is one of the most common reasons for therapeutic cannabis use. OBJECTIVES: To describe therapeutic cannabis use among patients with chronic pain. METHODS: Patients with chronic pain who voluntarily indicated that they used cannabis therapeutically completed a questionnaire about the type of cannabis used, the mode of administration, the amount used and the frequency of use, and their perception of the effectiveness of cannabis on a set of pain-associated symptoms and side effects. The study was approved by the McGill University Health Centre Research Ethics Board. RESULTS: Fifteen patients (10 male) were interviewed (median age 49.5 years, range 24 to 68 years). All patients smoked herbal cannabis for therapeutic reasons (median duration of use six years, range two weeks to 37 years). Seven patients only smoked at night-time (median dose eight puffs, range two to eight puffs), and eight patients used cannabis mainly during the day (median dose three puffs, range two to eight puffs); the median frequency of use was four times per day (range one to 16 times per day). Twelve patients reported improvement in pain and mood, while 11 reported improvement in sleep. Eight patients reported a 'high'; six denied a 'high'. Tolerance to cannabis was not reported. CONCLUSIONS: The results of this self-selected case series must be interpreted with caution. Small doses of smoked cannabis may improve pain, mood and sleep in some patients with chronic pain. Clinical trials are warranted to test these effects. Further prospective studies should examine the patterns and prevalence of cannabis use among chronic pain populations.